Study of Gasoline Engine Speed by Controlling Position of Idle Speed Control Valve - Jaiyong, Akenarong (Frontiers in Engineering Innovation Research, 2019)
The objective of this research was to design a gasoline engine speed control system by using Idle Speed Control Valve (ISCV). The engine of interest was a 115 cc. single-cylinder YAMAHA engine with a carburetor. It was modeled as a first-order linear system for simplicity, and was verified by using MATLAB R2011a. Using the C programming language, a dsPIC30F4011 microcontroller was programmed as the controller. The Chien-Hrones-Reswick (CHR) graphical techniques were used to obtain the PID controller gains when unit step reference inputs were applied to the control system. For this, two possibilities associated with the CHR technique were examined, namely PID 20% overshoot and PID least overshoot. It was found that the PID least overshoot method yielded satisfactory overshoot and performance. Performance of the control system was examined in three experiments. These included constant engine speed control, increasing speed control, and breaking disturbance rejection. It appeared from these experiments that, the output of the system could reach a constant speed reference input within 1.9 seconds, with no overshoot. The breaking disturbance was rejected within 6 seconds.